2014
DOI: 10.1177/1745691614545653
|View full text |Cite
|
Sign up to set email alerts
|

Registered Replication Report

Abstract: Trying to remember something now typically improves your ability to remember it later. However, after watching a video of a simulated bank robbery, participants who verbally described the robber were 25% worse at identifying the robber in a lineup than were participants who instead listed U.S. states and capitals-this has been termed the "verbal overshadowing" effect (Schooler & Engstler-Schooler, 1990). More recent studies suggested that this effect might be substantially smaller than first reported. Given un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(40 citation statements)
references
References 8 publications
1
37
0
2
Order By: Relevance
“…In addition, there have been several been high-profile, preregistered, multi-lab failures to replicate wellknown effects psychology (Eerland et al, 2016;Hagger et al, 2016;Wagenmakers et al, 2016). A similar multi-lab replication psychology that was considered successful yielded an effect size that was much smaller than the original (Alogna et al 2014). These findings have engendered pessimism about reproducibility.…”
mentioning
confidence: 87%
“…In addition, there have been several been high-profile, preregistered, multi-lab failures to replicate wellknown effects psychology (Eerland et al, 2016;Hagger et al, 2016;Wagenmakers et al, 2016). A similar multi-lab replication psychology that was considered successful yielded an effect size that was much smaller than the original (Alogna et al 2014). These findings have engendered pessimism about reproducibility.…”
mentioning
confidence: 87%
“…The more findings you publish, the more independent replications you need to execute and publish for everyone to benefit from a self-correcting cumulative knowledge base. 2 Another parallel between the peer review and replication norm worth mentioning is that in each case, researchers' primary motivation to embrace the norm is that they intrinsically care about the theoretical progress of their own research area. Hence, even though engaging in such activities takes time away from doing their own research, it is nonetheless in their best interest to peer-review and replicate other researchers' findings.…”
Section: New Replication Normmentioning
confidence: 99%
“…For instance, Perspectives on Psychological Science (PPS) now offers a new article type called Registered Replication Reports that involve multi-lab pre-registered replication attempts of important findings in psychology [90]. The process involves one lab submitting a proposal to replicate a finding that is deemed important (either theoretically influential or having important societal implications) which has yet to be independently replicated and/or still has substantial uncertainty about the size of the effect (e.g., multisite replication of verbal overshadowing effect [2]). Once a replication proposal is accepted and all procedures/ materials are finalized, PPS makes a public announcement, at which time other labs (typically about 15) can join in to contribute a sample to the replication effort and earn co-authorship on the final article.…”
Section: New Replication Normmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several recent, high-profile, large-scale research projects have demonstrated the potential of crowdsourcing research resources to make substantial contributions (e.g., the "Many Labs" projects, Ebersole et al, 2016;Eerland et al, 2016;Klein et al, 2014;Registered Replication Reports [RRR], Alogna et al 2014;Cheung et al, 2016;Hagger et al, 2016;Wagenmakers et al, 2016;"The Pipeline Project," Schweinsberg et al, 2016; the "ManyBabies" project, Frank et al, 2017; see also Schmalz, 2016). In each of these projects, several research teams each conducted a study (a) following the same methods, (b) at different locations and with different samples, and (c) the results from each research team were aggregated into a planned, common analysis from the project's inception.…”
mentioning
confidence: 99%